Kebijakan Politik Koperasi Merah Putih dalam Meningkatkan Kesejahteraan Keluarga Perspektif As-Siyasah Asy-Syar’iyah - Zulia Khoirun Nisa (LPPM UNU BLITAR, 2026)
The Merah Putih Village/Urban Community Cooperative policy represents a strategic initiative of the Indonesian government to strengthen village-based people-centered economic development, with the primary aim of enhancing family welfare as the foundation of socio-economic development. This article examines the political framework of the Merah Putih Cooperative in promoting family welfare and assesses its compatibility with the principles of As-Siyāsah al-Shar‘iyyah, particularly through the lens of Ibn Khaldun’s political-economic thought. Employing a qualitative library research approach, the study draws on statutory regulations, government policy documents, and classical as well as contemporary literature on people-centered economics and siyāsah shar‘iyyah. The findings indicate that the policy functions as a state-led political–economic instrument to strengthen family economic resilience through the empowerment of micro and small enterprises, inclusive access to capital, and the development of community-based economic networks. From the perspective of As-Siyāsah al-Shar‘iyyah, the policy holds normative legitimacy insofar as it reflects the state’s role as ḥāris al-maṣlaḥah, promotes distributive justice (al-‘adl), and protects community wealth (ḥifẓ al-māl). However, state intervention must remain facilitative and corrective to avoid undermining cooperative autonomy and democratic participation. Thus, the effectiveness of the Merah Putih Cooperative in enhancing family welfare depends on accountable governance, limited politicization, and consistent implementation aligned with the ethical principles of As-Siyāsah al-Shar‘iyyah.